Hydrogen Sulfide Inhibits High-Salt Diet-Induced Myocardial Oxidative Stress and Myocardial Hypertrophy in Dahl Rats - Huang, Pan; Shen, Zhizhou; Yu, Wen; Huang, Yaqian; Tang, Chaoshu; Du, Junbao; Jin, Hongfang (Frontiers in Pharmacology, 2017)
The study aimed to examine the protective effect of hydrogen sulfide (H2S) on high-salt-induced oxidative stress and myocardial hypertrophy in salt-sensitive (Dahl) rats. Thirty male Dahl rats and 40 SD rats were included in the study. They were randomly divided into Dahl control (Dahl + NS), Dahl high salt (Dahl + HS), Dahl + HS + NaHS, SD + NS, SD + HS, SD + HS + NaHS and SD + HS + hydroxylamine (HA). Rats in Dahl + NS and SD + NS groups were given chow with 0.5% NaCl and 0.9% normal saline intraperitoneally daily. Myocardial structure, α-myosin heavy chain (α-MHC) and β-myosin heavy chain (β-MHC) expressions were determined. Endogenous myocardial H2S pathway and oxidative stress in myocardial tissues were tested. Myocardial H2S pathway was downregulated with myocardial hypertrophy featured by increased heart weight/body weight and cardiomyocytes cross-sectional area, decreased α-MHC and increased β-MHC expressions in Dahl rats with high-salt diet (all P < 0.01), and oxidative stress in myocardial tissues was significantly activated, demonstrated by the increased contents of hydroxyl radical (•OH), malondialdehyde (MDA) and oxidized glutathione (GSSG) and decreased total antioxidant capacity (T-AOC), carbon monoxide (CO), catalase (CAT), glutathione (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) activities and decreased SOD1 and SOD2 protein expressions (P < 0.05, P < 0.01). However, H2S reduced myocardial hypertrophy with decreased heart weight/body weight and cardiomyocytes cross-sectional area, increased α-MHC, decreased β-MHC expressions and inhibited oxidative stress in myocardial tissues of Dahl rats with high-salt diet. However, no significant difference was found in H2S pathway, myocardial structure, α-MHC and β-MHC protein and oxidative status in myocardial tissues among SD + NS, SD + HS and SD + HS + NaHS groups. HA, an inhibitor of cystathionine β-synthase (CBS), inhibited myocardial H2S pathway (P < 0.01), and stimulated myocardial hypertrophy and oxidative stress in SD rats with high-salt diet. Hence, H2S inhibited myocardial hypertrophy in high salt-stimulated Dahl rats in association with the enhancement of antioxidant capacity, thereby inhibiting oxidative stress in myocardial tissues.